Rancang Bangun Penerangan Umum Berbasis Keamanan Masyarakat dalam Meningkatkan Perekonomian Daerah - Wiwin Windihastuty; Didik Hariyadi Raharjo (Yayasan REDI Tiga Monas, 2024)
Girijaya Village, Saketi District, Pandeglang Regency, where most of the roads are still uneven ground with valleys and hills next to the road covered with large trees and no street lighting, this makes people reluctant to carry out activities until evening. This prompted the community service team from Budi Luhur University to build lighting on the road. The method used is Participatory Action Research (PAR) where the community is actively involved in identifying and solving. The aim of community service is to improve community conditions through active participation from the community independently. Apart from that, the community is invited to improve its ability to solve its problems. A number of lighting lights were successfully implemented at previously mapped points. Road conditions are now clear and people are not worried about going home until late in the evening. Supervision and maintenance as well as development of public street lighting must be maintained and improved. It requires an active role from the community and can be used as further community service to completely resolve the lighting problem on the public roads in Girijaya Village.